2011
DOI: 10.1538/expanim.60.47
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Short Period Vasectomy on FSH, LH, Inhibin and Testosterone Secretions, and Sperm Motility in Adult Male Rats

Abstract: The present study was undertaken to clarify changes in secretions of FSH, LH, inhibin and testosterone, and sperm motility after bilateral vasectomy in adult male rats. Bilateral vasectomy was created surgically (treated group) and intact rats were used as control (control group). On days 3,5,7,14,30, 60, and 90 after surgery, plasma concentrations of FSH, LH, inhibin, and testosterone were measured by radioimmunoassay, and sperm motility characteristics were measured by computer-assisted sperm analysis (CASA)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 51 publications
(54 reference statements)
1
12
0
Order By: Relevance
“…reported that vasectomy did not affect testosterone levels. However, other studies have reported a significant reduction in testosterone during the early stages after vasectomy 43. Our data demonstrate that testosterone decreases significantly after vasectomy and gradually returns to baseline levels.…”
Section: Discussionsupporting
confidence: 55%
“…reported that vasectomy did not affect testosterone levels. However, other studies have reported a significant reduction in testosterone during the early stages after vasectomy 43. Our data demonstrate that testosterone decreases significantly after vasectomy and gradually returns to baseline levels.…”
Section: Discussionsupporting
confidence: 55%
“…A significant increase in epididymal weight was seen in vasectomized mice in comparison to the control group. Ren et al (2011a) reported a significant increase of epididymal weight in vasectomized group until 30 days post operation compared with control group as well. However, the weights of epididymis decreased from 30 days post operation compared with control group.…”
Section: Discussionmentioning
confidence: 84%
“…This effect of vasectomy has been reported in other studies as well. For example, Ren et al (2011a), who investigated the effect of short period vasectomy on sperm motility in adult male rats, found that vasectomy can harm spermatogenesis, reducing sperm motility starting from day 60 after vasectomy. Silber et al (1995), have suggested that in cases of chronically obstructed epididymis, sperm suffer changes related to old age with a significant decrease in motility towards the distal part.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, loss of Bbx caused azoospermia and infertility. Aberrant multinucleated giant cells were previously observed in rats with vasectomy-induced spermatogenic impairments [31]. In addition, genetically modified mice, such as Crem - [29, 30], Trf2 - [32], and Fdnc3a -deficient mice [33], display spermatogenic defects with aberrant multinucleated giant cells in the seminiferous tubules.…”
Section: Discussionmentioning
confidence: 99%